إجراءات البحث و التحري في الجريمة المعموماتية - ولد بن عمي العربي د. عمارة عمار - تركي محمد عالء الدين (جامعة المسيلة, 2024)
تعتبػر الجريمػة المعموماتيػة مػف الجػرائـ الجديػدة التػي أفرزتيػا تكنولوجيػات اإلعػالـ و االتصػاؿ الحديثػة و التػي باتػت تشػكؿ خطػرا عمػى المجتمػع الجزائػري وذلػؾ نظػرا الختالفيػا عػف بػاقي الجػرائـ التقميدية األخرى في طبيعتيا المتميزة و نقص التبميغ عنيا و سيولة إخفػاء أثارىػا واألجيػزة المخولػة بػالتحقيؽ و البحػث و التحػري الكتشػافيا ومكافحتيػا باإلضػافة إلػى اخػتالؼ أسػاليب ارتكابيػا ،إذ لػـ يكتؼ التشريع بتجريميا في قانوف العقوبات وقانوف اإلجراءات بؿ تعػداه ألكثػر مػف ذلػؾ حيػث عمػد المشػػرع الجزائػػري إلػػى اسػػتحداث نصػػوص قانونيػػة و إجػػراءات وكػػػذا إنشػػاء ىيئػػات ومؤسسػػات لمكافحتيا و اكتشافيا لمتصدي ليا بأحدث الوسائؿ التقنية. ABSTRACT : Information crime is considered one of the new crimes produced by modern media and communication technologies, which has become a threat to Algerian society due to its difference from other traditional crimes in its distinct nature, lack of reporting of it, ease of concealing its traces, and the agencies authorized to investigate, research and investigate to discover and combat it, in addition to the different methods. Committing it, as the legislation did not limit itself to criminalizing it in the Penal Code and the Procedural Code, but it went beyond that, as the Algerian legislator intended to create legal texts and procedures, as well as establishing bodies and institutions to combat it and discover it in order to confront it with the latest technical means.